2016
DOI: 10.3847/0004-637x/830/2/146
|View full text |Cite
|
Sign up to set email alerts
|

3d Pic Simulations of Collisionless Shocks at Lunar Magnetic Anomalies and Their Role in Forming Lunar Swirls

Abstract: Investigation of the lunar crustal magnetic anomalies offers a comprehensive long-term data set of observations of small-scale magnetic fields and their interaction with the solar wind. In this paper a review of the observations of lunar mini-magnetospheres is compared quantifiably with theoretical kinetic-scale plasma physics and 3D particlein-cell simulations. The aim of this paper is to provide a complete picture of all the aspects of the phenomena and to show how the observations from all the different and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…In this work, we have shown that the critical obstacle size for the formation of shocks in mini magnetospheres is L eff /ρ i > 1, resorting to massively parallel full PIC simulations. While the formation of a density cavity has been observed at sub-ρ i obstacles (in agreement with previous works 26,27,29 ), we observe a distinct behaviour when L/ρ i > 1, with ions being able to recirculate in front of the obstacle, and ultimately enhancing the plasma compression in this region. We have demonstrated that the ratio L eff /ρ i can be controlled by both the dipolar moment and the ion Larmor radius (or equivalently the flow Alfvènic Mach number).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this work, we have shown that the critical obstacle size for the formation of shocks in mini magnetospheres is L eff /ρ i > 1, resorting to massively parallel full PIC simulations. While the formation of a density cavity has been observed at sub-ρ i obstacles (in agreement with previous works 26,27,29 ), we observe a distinct behaviour when L/ρ i > 1, with ions being able to recirculate in front of the obstacle, and ultimately enhancing the plasma compression in this region. We have demonstrated that the ratio L eff /ρ i can be controlled by both the dipolar moment and the ion Larmor radius (or equivalently the flow Alfvènic Mach number).…”
Section: Discussionsupporting
confidence: 92%
“…This macroscopic picture has an underlying, well understood microscopic equivalent 26,29 . As the plasma approaches the steep gradient of the magnetic field at the magnetopause, it is slowed down due to a ponderomotivelike force (∇B 2 ).…”
Section: Shock Formation In Mini Magnetospheresmentioning
confidence: 99%
“…Following from several magnetometer‐based studies of magnetic field structure (Hemingway & Garrick‐Bethell, ; Shibuya et al, ; Tsunakawa et al, ), together with a series of hybrid and kinetic plasma simulations (e.g., Bamford et al, , ; Deca et al, ; Poppe et al, , ; Zimmerman et al, ), we use lunar swirl morphology as a proxy for the structure of near‐surface magnetic fields. This allows us to place strong constraints on the geometry of the underlying magnetic source bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Roughly speaking, portions of the surface with open magnetic field lines may be expected to experience normal or even accelerated solar wind‐related space weathering, leading to darkening, whereas portions of the surface beneath closed magnetic field lines should experience greater protection from solar wind weathering, thus remaining relatively bright (Hemingway & Garrick‐Bethell, ). Indeed, magnetometer‐based studies of magnetic field structure (Hemingway & Garrick‐Bethell, ; Shibuya et al, ; Tsunakawa et al, ), as well as hybrid and kinetic plasma simulations (e.g., Bamford et al, , ; Deca et al, , ; Fatemi et al, ; Giacalone & Hood, ; Jarvinen et al, ; Poppe et al, , ; Zimmerman et al, ), indicate that swirl morphology may be dictated by magnetic field topology in precisely this way. It has also been proposed that swirls may be the result of electrostatic (Garrick‐Bethell et al, ) or magnetic (Pieters et al, ) sorting of fine‐grained materials, rather than of deflection of solar wind.…”
Section: Introductionmentioning
confidence: 99%
“…Reiner Gamma is perhaps the most well-known magnetic anomaly, but no theory for its formation has been accepted. Here we propose a formation model informed by its uniquely symmetric albedo markings (known as swirls; Figure 1a), which likely arise from the crustal field limiting solar wind access to the surface (Bamford et al, 2016;Deca et al, 2018;Hood, Coleman, Russell, & Wilhelms, 1979;Hood & Schubert, 1980;Poppe et al, 2016). Hemingway and Garrick-Bethell (2012), hereafter HGB12, showed that horizontal fields are likely associated with bright parts of the swirl, while weak horizontal fields may create cusp regions that permit the solar wind to access and darken the surface (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%